Way forward to halt pressure loss in automotive tyres - Subramonian, Sivarao; Raguvaran, Jayahkudy; Md Ali, Mohd Amran; T., Joseph Sahaya Anand; Qumrul, Ahsan; Raja, Izamshah (Trans Tech Publications, 2015)
Tyre is one of the most crucial components in a vehicle structure not only to have the vehicle running smoothly on the road, but also to provide physical and acoustic comfort for the passengers. But, since the day the inflatable tyres were invented, sudden loss of air in a tyre acts as a major problem associated with tyres; and are still being treated to date by professional researchers and giant tyre manufacturers. The phenomena where tyre experiences natural pressure loss over the time is called air permeation which causes tyre to deflate on its own. Besides reviewing the primary theories and findings that contribute to natural air permeation that literally causes the pressure drop of an automotive tyre, this paper also reveals the experimentally validated results of the significant factor which contributes to air permeation of an automotive tyre. Additionally, a relevant nano-based solution to reduce the air permeation rate to stop the tyre deflation is also highlighted to establish the way forward total solution suiting wide range of tyres used on domestic cars.